2007
DOI: 10.1248/cpb.55.666
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperoxysterols from the Tunicate Eudistoma sp.

Abstract: Tunicates have been well-recognized as marine organisms containing large quantities of secondary metabolites that exhibit varying degrees of biological activities. 1,2) In connection with our continuing investigations of bioactive substances from marine organisms, a tunicate Eudistoma species (subphylum Urochordata, class Ascidiacea, order Enterogona, suborder Aplousobranchiata, family Polycitoridae) was selected for study, 3,4) as the EtOAc extract of this organism was found to exhibit cytotoxicity against MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Two isomeric hydroperoxides, 625 and 626, previously reported as synthetic products, were isolated as mildly cytotoxic metabolites of a Taiwanese collection of Eudistoma sp. 391 Three cytotoxic oxygenated fucosterols 627-629 were obtained from the marine brown alga Turbinaria conoides. 392 A Formosan soft coral sinularia sp.…”
mentioning
confidence: 99%
“…Two isomeric hydroperoxides, 625 and 626, previously reported as synthetic products, were isolated as mildly cytotoxic metabolites of a Taiwanese collection of Eudistoma sp. 391 Three cytotoxic oxygenated fucosterols 627-629 were obtained from the marine brown alga Turbinaria conoides. 392 A Formosan soft coral sinularia sp.…”
mentioning
confidence: 99%
“…The most plausible biosynthetic pathway for 1 and 2 in sponge involves the abstraction of an allylic proton by an activated oxygen, such as O 2 , along with migration of the carboncarbon double bond (Figure 2). Several naturally occurring hydroperoxy steroids have been isolated from tunicates (Sung et al, 2007), seaweeds (Teixeira et al, 2006), algae (Sheu et al, 1997a,b) and some plants (Kato et al, 1996), supporting the assumption that these compounds are not artifacts. We propose that the bioactive and unstable steroid can be biosynthesized in sponge under a special ecological environment to act as a defensive strategy against invaders.…”
Section: Resultsmentioning
confidence: 94%
“…70 Despite the fact that similar compounds were isolated from other plants and marine animals, 118 and proved to have significant biological activities, a follow-up study was never reported. It is worth trying to find this compound family in other Arum subspecies, characterize them and test them for biological activities, especially antimicrobial and antifungal activities.…”
Section: Figure 3 Structures Of T-cadinol and T-muurololmentioning
confidence: 99%